Pendampingan Orang Tua dan Anak dalam Mengembangkan Kreativitas Anak Melalui Kegiatan Kolase Mamamia di TK Ihyaul Ulum Lamongan - Saadah, Dwi Aminatus; Misbahul Huda; Desi Ismawati; Supriyanto; Anikmah (STAI Ma'had Aly Al-Hikam Malang, 2025)
Abstract The low involvement of parents in assisting early childhood creative activities is still an important issue in the world of children's education. The focus of this service is to increase the active role of parents in developing children's creativity through mammal collage activities. The purpose of this pkm is to empower parents and children to create fun and meaningful educational interactions through the media of Mamamia collage. This service was carried out at Ihyaul Ulum Lamongan Kindergarten involving 30 parents and 30 children aged 4-6 years. The approach used is Participatory Action Research (PAR), with implementation methods in the form of socialization, Mammomia collage training, collaborative practices of parents and children, and participatory evaluation. The results of the service showed an increase in parental involvement in the child's learning process at school and the formation of closer communication between parents and children. It can be concluded that this pkm activity is effective in encouraging family involvement in early childhood education and building collective awareness towards social transformation in the PAUD environment. Keywords: Children's Creativity, Mammal Collage, Early Childhood Education. Abstrak Rendahnya keterlibatan orang tua dalam mendampingi aktivitas kreatif anak usia dini masih menjadi isu penting dalam dunia pendidikan anak. Fokus pengabdian ini adalah meningkatkan peran aktif orang tua dalam mengembangkan kreativitas anak melalui kegiatan kolase mamamia. Tujuan pkm ini dalah mendampingi orang tua dan anak untuk menciptakan interaksi edukatif yang menyenangkan dan bermakna melalui media kolase Mamamia. Pengabdian ini dilakukan di TK Ihyaul Ulum Lamongan dengan melibatkan 30 orang tua dan 30 anak usia 4–6 tahun. Pendekatan yang digunakan adalah Participatory Action Research (PAR), dengan metode pelaksanaan berupa sosialisasi, pelatihan kolase Mamamia, praktik kolaboratif orang tua dan anak, serta evaluasi partisipatif. Hasil pengabdian menunjukkan adanya peningkatan keterlibatan orang tua dalam proses pembelajaran anak di sekolah dan terbentuknya komunikasi yang lebih erat antara orang tua dan anak. Dapat disimpulkan bahwa kegiatan pkm ini efektif dalam mendorong keterlibatan keluarga dalam pendidikan anak usia dini serta membangun kesadaran kolektif menuju transformasi sosial di lingkungan PAUD. Kata Kunci: Kreatifitas Anak, Kolase Mamamia, PAUD